Estimating the distribution of wealth in New Zealand - Benjamin Ching; Tayla Forward; Oscar Parkyn (New Zealand Government, The Treasury, 2023)
This paper discusses alternative methods to estimate the distribution of wealth in New Zealand. It develops a taxable income capitalisation method for estimating the distribution of wealth in New Zealand that is based on the approach of Saez and Zucman (2016; 2022) and adapted for New Zealand data sources, which we term "the New Zealand capitalisation method". Internationally, taxable income capitalisation has been found to be a high-performing method for estimating asset holdings that generate taxable income flows, particularly towards the top of the wealth distribution where household surveys often undercount wealth. The New Zealand capitalisation method combines Inland Revenue taxable income administration data with Stats NZ's Household Balance Sheet to give new estimates of the distribution of New Zealand individuals' wealth. We present results for 2010, 2015, and 2018, and compare these distributions with those recorded by the Household Economic Survey (HES) 2018. Our method also allows for wealth estimates of smaller groups than can be reliably obtained through HES, including estimates of the wealth held by the top 0.1% of the wealth distribution. The New Zealand capitalisation method suggests more wealth at the top of the distribution than estimated by HES, which is consistent with similar work internationally. Results also show that wealth shares at the top of the distribution fell between 2010 and 2018, while at the same time the greatest increase in average wealth went to the top of the distribution.
Keywords: D31; E01; E21; H2; N37; 330; Wealth; distribution; inequality; capitalisation; New Zealand